ANALISIS KESALAHAN DALAM PENULISAN KARANGAN NARASI SISWA SEKOLAH DASAR KELAS TINGGI - Zahrah, Firdha; Taofik; Soleh, Dudung Amir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Writing narrative skills are crucial in developing language abilities; however, manystudents face difficulties in writing narrative compositions correctly. This study aimsto analyze the errors in narrative composition writing among upper-gradeelementary school students. The research uses a literature review method, whichinvolves planning, searching and selecting, analysis, and synthesis stages. Thesearch was conducted through Google Scholar, limited to national journals indexedin SINTA 1-6 from 2021 to 2025, resulting in 10 relevant journals. The findings showthat the most frequent errors are the improper use of capital letters, punctuationmarks, inaccurate word choices, ineffective sentence structures, and insufficientdevelopment of the composition's content. These errors reflect students' weakunderstanding of linguistic rules and narrative elements. This study recommends astep-by-step and continuous writing learning process to help students improve theirwriting skills comprehensively.